Kepemimpinan Manajer BMT Amanah Ummah dalam Meningkatkan Kinerja Karyawan - Baidowi R., Nor; , Dr. Muhtarom, SH., MH (2017)
The target of this research is to know leadership of manager of Bait al-Māl wa al-Tamwil (BMT, House of Money and Finance) Amanah Ummah and success of leadership applied by BMT Amanah Ummah in improying employees performance. This research represent field research with descriptive and qualitative data analysis. The are obtained from observation, interview, and documentation which researcher does in BMT Amanah Ummah directly. To conclude from data, researcher use deductive-inductive. As conclusion of this research, the leadership style applied in BMT Amanah Ummah is effective enough, refered to the leadership theory of Rasulullah PuH. In improving all employees performance, their motivation, and their performance stability. Moreover, as the impact of such leadership, BMT Amanah Ummah has reached best progress. Keyword: leadership, leadership style, employees performance.